Survey among BNS supervisors on the implementation of PD 1569 in selected areas in the Philippines - Garcia, Lorna O.; Talavera, Ma. Theresa M.; Bustos, Angelina R.; Africa, Leila S.; Felix, Angelina dR. (2011)
The survey among BNS Supervisors on the implementation of Presidential Decree (PD) 1569 "Strengthening the Barangay Nutrition Program by Providing for a Barangay Nutrition Scholar in Every Barangay, Providing Funds Thereof, and for Other Purposes" was assessed through a survey completed by 178 out of the 209 trainers/supervisors of barangay nutrition scholars (BNSs) who participated in the different batches of Training of Trainers on Basics Course for BNSs, but excluding those from the Autonomous Region of Muslim Mindanao.

Almost all (98%) of the respondents' trainers/supervisors cited presence of at least one BNS in their areas of assignments. Other provisions of the law particularly those that relates to the recruitment/selection/hiring of BNSs, their benefits, trainings and supervision were also implemented but not consistent and were in varying extent.

Overall, there is a need to introduce amendment to the law to strengthen the BNS program to further improve the nutrition situation in the Philippines. Priority should be given to standardizing qualifications, duties and benefits of BNSs be revised to at least reaching secondary school and the benefits be parallel to those received by other community workers in the areas, such as Barangay Health Workers and Barangay Nutrition Action Officers.
Keywords: Nutritional assessment